Robust longitudinal spin-Seebeck effect in Bi-YIG thin films - Siegel, Gene (Nature Publishing Group, 2014)
In recent years, the coupling of magnetic insulators (bismuth-doped yttrium iron garnet, Bi-YIG) with platinum has garnered significant interest in spintronics research due to applicability as spin-current-driven thermoelectric coatings. These coatings bridge the gap between spintronics technologies and thermoelectric materials, providing a novel means of transforming waste heat into electricity. However, there remain questions regarding the origins of the spin-Seebeck effect (SSE) as well as claims that observed effects are a manifestation of magnetic proximity effects, which would induce magnetic behavior in platinum. Herewith we provide support that the voltages observed in the Bi-YIG/Pt films are purely SSE voltages. We reaffirm claims that magnon transport theory provides an ample basis for explaining SSE behavior. Finally, we illustrate the advantages of pulsed-laser deposition, as these Bi-YIG films possess large SSE voltages (even in absence of an external magnetic field), as much as twice those of films fabricated via solution-based methods.